The Environment in Global Sustainability Governance Perceptions, Actors, Innovations - Partzsch, Lena (Bristol University Press, 2023)
EPDF and EPUB available Open Access under CC-BY-NC-ND license. With Agenda 2030, the UN adopted wide-ranging Sustainable Development Goals (SDGs) that integrate development and environmental agendas. This book focuses on the political tensions between the environmental objectives and socio-economic aspects of sustainable development. The collection provides an introduction to interlinkages, synergies and trade-offs between the 'green' and other goals, such as gender equality and economic growth. It also considers related goals on cities and partnerships as crucial for implementing environmentally sound sustainability. Identifying governance failures and responsibilities, it advocates for a shift towards cooperative economics and politics for the common good.